Reticulated Open-Celled Zinc Oxide Ceramic Foams: Manufacturing, Microstructure, Mechanical, and Thermal Properties - Ulf Betke; Michael Scheffler (Advances in Materials Science and Engineering)
Open-celled zinc oxide ceramic foams were prepared by the polymer sponge replication (Schwartzwalder) technique from aqueous ZnO dispersions with Sb2O3 and Bi2O3 as sintering additives, and mechanically stable ZnO foams with an average porosity of 93.6% were obtained. Their microstructure consists of ZnO grains with a Bi-containing grain boundary phase together with a Zn-Sb-O secondary phase with spinel structure. The obtained ZnO ceramic foams were characterized with respect to their morphology by computed tomography; in addition, the compressive strength and the thermal conductivity were determined, and the data were applied for modelling of the mechanical and thermal properties of the bulk ZnO strut material.